PENGARUH TERAPI MUSIK DEGUNG TERHADAP TINGKAT NYERI PADA PASIEN POST ORIF (OPEN REDUCTION AND INTERNAL FIXATION) FRAKTUR EXTREMITAS BAWAH DI RSUD KABUPATEN TANGERANG - Wahyuningsih, Tuti; Warongan, Anwar Wardi; Rayansari, Fitrian (Universitas Islam Negeri Alauddin Makassar, 2020)
A fracture known as a fracture is a disorder of continuity of bone and soft tissue around it. One of the measures for the treatment of fractures is surgery called Open Reduction Internal Fixation (Orif). As a result, Orif can cause pain side effects. Various attempts were made to overcome post Orif pain one of them with degung music therapy. Degung music is one of the complementary therapies that can be used to reduce the level of pain in post Orif patients. This study aims to determine the effect of degung music therapy on reducing pain levels in post Orif patients. The study design used a quasi experiment with a non equivalent control group pre-test and post- test approach with 12 respondents in the intervention group and 12 respondents in the control group. The results show that there is an effect of degung music therapy on the level of post Orif pain in the intervention group (p = 0.003) and there is an effect of standard therapy in the control group (p = 0.003) and there is a difference in the effect of degung music therapy in the intervention group with the standard therapy in the control group ( 0.045), with the results obtained in the control group the average difference in post Orif pain levels was 0.75, while in the intervention group was 1.58. The conclusion of this study is that degung music therapy can reduce pain levels in post Orif patients, so that degung music therapy can be used as a complementary therapy option to reduce pain levels in post Orif patients .